Stakeholders' willingness to pay for enhanced construction waste management: A Hong Kong study. (July 2015) - Lu, Weisheng; Peng, Yi; Webster, Chris; Zuo, Jian
Abstract: Based on the polluter pays principle, construction waste disposal charging schemes (CWDCS) have been deployed by various economies as one of the most effective ways of managing construction waste. Nevertheless, a means of rationalizing these schemes has not been well documented. Using the economic technique of contingent valuation method (CVM), this study aims to investigate stakeholders' willingness to pay (WTP) for enhanced construction waste management (CWM) with a view to providing a scientific foundation for CWDCS rationalisation. In considering this WTP in light of repeated exhortations that all stakeholders play a role in the management of construction waste, the study is unique. To ascertain stakeholders' WTP, a payment card-style questionnaire survey was designed and administered to Hong Kong's major CWM stakeholders in February 2014. Interestingly, the results show that there is no statistically significant variation in the WTP expressed by different stakeholder groups. The average maximum WTP is around HK232/t for landfill disposal of construction and demolition (C&D) waste, HK186/t for off-site sorting facility (OSF) disposal, and HK120/t for public fill reception facility (PFRF) disposal. These values are higher than the existing CWDCS charges (HK125/t for land filling, HK100/t for OSF disposal, and HK27/t for PFRF disposal) but much lower than the charges proposed to the government. This research provides not only a scientific foundation for the ongoing debate on changes to Hong Kong's CWDCS, but also a valuable reference for other economies facing the challenge of developing charging schemes to deal with construction waste.